Heathcliff’s multiple references in Emily Brontë’s Wuthering Heights - Ismail, Hisham Muhamad (Research Journal in Advanced Humanities, 2023)
Wuthering Heights is considered one of the most controversial novels in the history of English literature due to its debatable themes and other messages. However, the novel is examined intensively and receives many critical commentaries. The earliest reviewers show less interest in this novel and its themes. Moreover, they harshly criticize the aggressive depiction of the relations and the unfavorable portrayal of the female characters. On the other hand, other critics greatly praise the uniqueness and originality of the writing style and intelligent analysis of Victorian society. Between the two opposing views, the reader may understand that Emily Bronte wants to build this controversial status to shed light on the unspoken issues in British society during the Victorian era. One of the most attractive points in this novel is the skillful portrayal of the main character, Heathcliff. Bronte manipulates these characters cunningly to represent all of the drawbacks of society. She uses this character to criticize the nature of relationships, the social situation, the political aspect, and the economic status of British society at that time. Due to the multiple facets of this character, the reader may find it difficult to understand his behaviors, attitudes, and emotions. Bronte makes the reader fluctuate between loving and sympathizing with this character to hating and disagreeing with most of his deeds. These doubtable reactions towards this character may remain till the end of the novel. Undoubtedly, the reader may enjoy reading this novel and understand the nature of this complicated web of relationships and elicit unspoken messages.